Rotary Veneer Bentwood as a Sustainable Material for Responsible Furniture Production - Hartanto, Susi (Proceeding of International Joint Conference on UNESA, 2024)
The use of spindleless rotary peeling technology has revolutionized the processing of smaller diameter wood species like rubber wood and acacia, which were previously unable to be turned into rotary veneers using traditional methods that only accommodated larger diameter wood. This article is intended to provide valuable insights, particularly for furniture designers, on how to utilize environmentally friendly and efficient raw materials that retain the beauty of wood through 4 design cases (2 solid wood chair design & 2 bentwood chair design). The article was created through a descriptive analysis method, iterative design method, and material driven design method, which involved direct study and furniture design of mass-produced wooden furniture made from solid wood and prototype-scale bentwood furniture, as well as surveys of factories producing solid wood furniture and rotary veneers, and factories producing bentwood furniture. With comparison of all 4 designs, it is concluded that manufacturers can achieve a more sustainable, efficient, and environmentally friendly option for material, parts, and hardware usage by using rubber wood rotary veneer bentwood as the main material. Design, in terms of 3D production, rendering, technical drawings, assembly instruction also take less time to produce compare to furniture designs in solid wood material. In short, the use of rotary veneer bentwood is highly encouraged over solid wood, to support Sustainable Development Goal (SDG) 12 on responsible production.